TINJAUAN YURIDIS ATAS GUGURNYA HAK UNTUK MENUNTUT PIDANA MENURUT UNDANG-UNDANG HUKUM - Syamsul Bahri, Nur Cahya Dian Sahputra dan (Universitas 17 Agustus 1945 Samarinda, 2020)
In order to complete studies at the University of Law Faculty of August 17, 1945 Samarinda, one of the tasks that must be completed is scientific writing, this imiah writing is entitled: